The implementation of sumedang jaya wisata (sjw) management in supporting the development of halal tourism in ranah pesisir, west sumatra - Faisal Efendi; Ikhwanuddin Abdul Majid; Nurlaila Nurlaila; Musa Zulkifli; Afrikal Candra; Nimuhammadfatin Samae; Aliwan (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to analyze the implementation of management at Sumedang Jaya Wisata (SJW) in supporting the development of community-based halal tourism in Pesisir Selatan Regency, West Sumatra. Halal tourism is understood as a destination management approach that not only emphasizes economic and aesthetic aspects but also highlights Islamic spiritual values such as cleanliness, trustworthiness, community participation, and environmental sustainability. This research uses a descriptive qualitative method with data collection techniques including field observations, in-depth interviews, and documentation. Research informants consist of SJW managers, business actors, and village officials directly involved in managing the tourism area. The results show that the management implementation at SJW includes key functions such as facility management, improved accessibility, delegation of authority, and tourism promotion. However, several challenges remain in implementation, particularly regarding the quality of human resources, limited budget, lack of technological innovation, low public awareness of public facility governance, and suboptimal promotion of halal tourism. Islamic values such as maslahah (public benefit), ukhuwah (brotherhood), muhasabah (self-reflection), and amanah (trust) have not yet been fully internalized into managerial practices. This study recommends the need for sharia-based tourism management training, strengthening of local halal tourism regulations, the formation of a community education team, and the digitalization of promotion and services. With more structured and Islamic value-based management, Sumedang Jaya Wisata has the potential to become a leading halal tourism destination that is competitive and sustainable.